A study on management of tennis elbow by local platelet rich plasma injection - Jan, Wazir Fahad; Jahan, Alamgir; Dar, Mohd Yahya; Khan, Umer Mushtaq (International Journal of Research in Orthopaedics, 2019)
Background: Lateral epicondylitis (tennis elbow), a familiar term used to describe myriad symptoms around the lateral aspect of the elbow can occur during activities that require repetitive supination and pronation of the forearm with the elbow in near full extension. This condition can cause severe discomfort to the patient resulting in debilitation and impairment of routine activities. The purpose of this study was to evaluate the effectiveness of local autologous platelet rich plasma injection in the treatment of tennis elbow. Methods: This was a prospective observational study conducted on 50 patients of either sex with an average age of 45.92 years, presenting to the Orthopaedic OPD of SHKM Government Medical College Hospital, Nalhar, NUH, Haryana between November 2016 and February 2018, with a diagnosis of lateral epicondylitis. All the patients were treated with local platelet rich plasma injection and the results were analysed through the assessment of visual analog score (VAS) and disability of arm shoulder and hand (DASH) score. The patients were followed up for a period of 6 months after the local injection of platelet rich plasma. Results: Majority of the patients had significant relief with this method. The VAS and DASH score improved from the pre-treatment values of 8.7 and 74.6 to 2.6 and 29.8 respectively, which was found to be statistically significant (p<0.001). Conclusions: Thus results of our study demonstrate that the local injection of platelet rich plasma is a safe and effective method of treatment of lateral epicondylitis.